Prosthetic rehabilitation of a patient with X-linked hypophosphatemia using dental implants: a case report and review of the literature - Martin James; Reza Vahid Roudsari (SpringerOpen, 2019)
Abstract Background X-linked hypophosphatemia is associated with a range of dental problems, many of which may result in early loss of the dentition. Most patients, but especially young adults, are likely to desire fixed prosthodontic replacements, and dental implants may be the preferred solution in many cases. The use of dental implants to rehabilitate this patient group has not been widely studied with the literature limited to a small number of case reports with limited follow-up. Case presentation This case report describes the dental journey of a young adult with X-linked hypophosphatemia, his eventual tooth loss and rehabilitation with multiple dental implants. Over 10 years' follow-up of three of the fixtures is presented. Conclusions This case report shows a common presentation and progression of a patient with X-linked hypophosphatemia and will hopefully provide further positive evidence for the clinician to rely on when considering dental implant based treatments for such patients.